Movement-specific keyboard playing for hand function in adolescents and young adults with acquired brain injury - Kim, Soo Ji; Shin, Yoon-Kyum; Jeong, Eomhyeong; Cho, Sung-Rae (Frontiers in Neurology, 2023)
Background Patients with acquired brain injury (ABI) suffer from deficits in fine motor function in hands which affect independent self-care function in daily life. This study aimed to examine the effects of movement-specific keyboard playing for improved hand function in adolescents and young adults with ABI. Method A total of 23 patients with ABI participated in this study. Twelve were assigned to the intervention group and eleven to the control group. The intervention group engaged in movement-specific keyboard playing three to four times a week for 3 weeks in addition to standard care, while the control group received only standard care. Results The results of a mixed model of repeated measures ANOVA showed that the time effects were significant in the functional independence measure, key-pressing force, and most of the hand function tests measured. In terms of the interaction effect between group and time, a significant effect was found only in the checker-stacking task as a subtest of the Jebsen-Talyor Hand Function Test. Discussion These results indicate that the specified movements required to play the keyboard may involve more precise and dexterous manipulation with hands and fingers. These results also suggest that movement-specific keyboard playing has potential in optimizing the intervention effect of keyboard playing while maximizing the benefits of music for motivating young patients with ABI.